Submerged microfiltration membrane and activated carbon processes for recalcitrant compounds removal in oil refinery effluent as electrodialysis pre-treatment - Carolinne Ragazzi Piombini (IWA Publishing, 2021)
The combination of suspended activated carbon (AC) and submerged microfiltration (SMF) processes was applied to polish a biotreated effluent generated in a refinery industry. Preliminary results indicated that Norit 1240 W AC was more suitable than Carbomafra AC brand for total organic carbon (TOC) removal due to the highest Freundlich adsorption constant value (1.97 ± 0.42 and 0.96 ± 0.23 (mg/g)(L/mg)1/n, respectively), thus the first one was used in the combined system. Among all particle sizes of AC tested (0.041–1.01 mm), AC/SMF system was better performed, according to permeation flux, when applying granular AC instead of the powder one. On the other hand, the best response regarding TOC removal and absorbance at 254 nm (ABS254 nm) reduction were observed when applying powder AC (89% and 97%, respectively). Statistical analysis with two-sample T-test (p-value <0.05) endorsed the need of both air purge (20 L/h) and backwash strategies (8 min of permeation and 10 seconds of backwash) to diminish fouling occurrence in the SMF system. Finally, it was found that 2 g/L of Norit 1240 W PAC (0.041 mm particle size) condition fitted the effluent to further electrodialysis reversal (EDR) process (3.4 mg/L TOC) with consistent normalized permeate flux after 5 h of permeation (0.76 ± 0.1 J/J0). HIGHLIGHTS Air purge and backwash was ultimately important to AC/SMF system to prevent membrane fouling.; AC/SMF system could effectively polish the biotreated refinery effluent to suit it to the EDR process.; Higher particle size of granular activated carbon (GAC) prevented permeate flux reduction.; AC/SMF system showed the possibility of replacing at least three consecutive processes in pilot-plant scale.;